Pengaruh Produk Domestik Bruto, Impor, dan Harga Minyak Dunia Terhadap Indeks Harga Saham Gabungan - Anggraeni, Laela; Sumantri, Fazhar; Halizah, Zahwa Nur; Rizqi, Muhammad (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2023)
The Composite Stock Price Index (JCI) is a series of historical information regarding the movement of the combined stock price of all stocks up to a certain date. This study aims to determine the effect of Gross Domestic Product (GDP), imports, and World Oil Prices on the Jakarta Composite Index (JCI) for the 2017-2021 period. The data used in this study is secondary data, which is quarterly data obtained from investing.com, the Central Statistics Agency (BPS), and the Ministry of Trade, which consists of 4 data each year. The research is quantitative or based on the results of calculations, with descriptive statistical calculation techniques. Based on the Adjusted R Square test, the result is 0.267 or 26.7%. This explains that the independent variables, namely Gross Domestic Product (GDP), Imports, and World Oil Prices affect the value of the dependent variable, namely the Composite Stock Price Index (JCI) by 26.7%. At the same time, the rest is influenced by the value of other variables not tested in this study. that is equal to 73.3% (100%-26.7%).